Osmotolerant yeast species differ in basic physiological parameters and in tolerance of non-osmotic stresses - Bubnová, Michala; Zemančíková, Jana; Sychrová, Hana (Yeast (Chichester, England), 2014)
Osmotolerance is the ability to grow in an environment with a high osmotic pressure. In this study we compared the physiological parameters and tolerance to osmotic and non-osmotic stresses of three osmotolerant yeast species, Debaryomyces hansenii, Pichia farinosa (sorbitophila) and Zygosaccharomyces rouxii, with those of wild-type Saccharomyces cerevisiae. Although the osmotolerant species did not differ significantly in their basic parameters, such as cell size or growth capacity, they had different abilities to survive anhydrobiosis, potassium limitation or the presence of toxic cationic drugs. When their osmotolerance was compared, the results revealed that some of the species isolated as sugar/polyol-tolerant (e.g. P. farinosa) are also highly tolerant to salts and, vice versa, some strains isolated from an environment with high concentration of salt (e.g. Z. rouxii ATCC 42981) tolerate high concentrations of sugars. None of the tested strains and species was osmophilic. Taken together, our results showed that P. farinosa (sorbitophila) is the most robust species when coping with various stresses, while Z. rouxii CBS 732, although osmotolerant in general, is not specifically salt-tolerant and is quite sensitive to most of the tested stress conditions.
Keywords: Polymers; metabolismus sacharidů; Osmotic Pressure; Stress, Physiological; osmotický tlak; desiccation survival; non-conventional yeasts; yeast osmotolerance; Saccharomycetales; oxidative stress; Salts; Microbial Viability; salt stress; soli; fyziologický stres; polymery; Carbohydrate Metabolism; mikrobiální viabilita